2014
DOI: 10.1016/j.jiph.2014.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of hepatitis C virus infection among inmates at two New York State correctional facilities

Abstract: Summary Previous studies have reported decreasing hepatitis C virus (HCV) infection rates in the general population. However, differential susceptibility in institutionalized populations suggest that HCV infection is even more prevalent in prison populations than previously reported yet, routine screening for HCV infection among prisoners is not generally available. We estimated the HCV prevalence and identified associated exposures at two maximum-security prisons using data obtained from 2788 inmates from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 19 publications
1
24
3
Order By: Relevance
“…in Iran, who reported HCV exposure prevalences of 7.7% and 7.8%. Studies in the United States have estimated the prevalence of this disease among prisoners as 10% . The estimates provided in some studies differ significantly from ours.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…in Iran, who reported HCV exposure prevalences of 7.7% and 7.8%. Studies in the United States have estimated the prevalence of this disease among prisoners as 10% . The estimates provided in some studies differ significantly from ours.…”
Section: Discussioncontrasting
confidence: 86%
“…The estimates of the prevalence of HCV exposure in the general prison population of Iran obtained in the present study are consistent with the estimates provided by Ziaee et al [29] and Azarkar et al [30] in Iran, who reported HCV exposure prevalences of 7.7% and 7.8%. Studies in the United States have estimated the prevalence of this disease among prisoners as 10% [31]. The estimates provided in some studies differ significantly from ours.…”
Section: Discussioncontrasting
confidence: 85%
“…When the prisons were examined in general; the prison inmates had risky behavioral patterns, violent tendencies, deviant sexual behavior and substance abuse; and it was found that the cleaning and hygiene procedures were not properly followed in the environments where such crowded groups live together with continued risky behaviors in prisons ( 4 ). Continued substance abuse in prisons by most of the drug addicts, common use of injection materials, tattoos and other circumstances that result in blood contact increase the risk of infections ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Where sex-specific prevalence rates were available, we calculated the M:F ratio of infected persons by multiplying the M:F prevalence in each study with sex-specific prevalence data 20,28,[32][33][34][35][36]38,[41][42][43][44][45]49,52,53,64,65 by the sex ratio of the population: M:F ratio of infected persons 5 M:F prevalence ratio 3 M:F sex ratio of population This is true because: For prison studies we used the sex ratio of the respective state prison system. For homeless studies we used the estimated overall national sex ratio.…”
Section: Appendix A: Sex Ratio Methodsmentioning
confidence: 99%